Chickpea breeding program and research in Portugal - Isabel Duarte (Open Journal of Plant Science - Peertechz Publications, 2022)
Chickpea (Cicer arietinum L.) is a very important crop in the world. Portugal was traditionally sown as a spring crop and so extremely affected by long periods of drought and temperature variation throughout the growth cycle. Chickpea grain yields decrease substantially due to increased air temperature and the severity of drought. To face the Mediterranean-type climate pattern, chickpea breeding programs were reoriented to develop chickpea germplasm tolerant/resistant to the main abiotic and biotic stress and adapted to different environments and production systems. This study relates chickpea yields (35 years) with rainfall average in Alentejo, a Southern Portugal region with a Mediterranean-type climate. Our approach shows that selection should apply multiple and complementary criteria. The physiological and morphological studies are important in breeding programs, to combine not only resistance to drought and temperature, and biotic stress but also high yield potential and yield stability. The main objective is to obtain new chickpea varieties for the rainfed conditions of the Mediterranean region. From this work, four chickpea varieties (Kabuli type), were registered on the National Variety Catalogue. Actually, the national chickpea genetic breeding program has already registered 11 varieties.